Dielectric properties of (1 - x)Pb(Zr0.52Ti0.48)O3-(x)BaTiO3ceramics under uniaxial compressive pre-stress - Rattikorn Yimnirun (2018)
Effects of uniaxial compressive pre-stress on the dielectric properties of ceramics in PZT-BT solid-solution system are investigated. The physical properties measurements reveal that the addition of BT into PZT results in the increase of grain size and microstructural heterogeneity, except for the density which sees the opposite trend. The dielectric properties measured under stress-free condition show a gradual increase of the dielectric constant with increasing BT content, while the dielectric loss tangent is not considerably different. The dielectric properties under the uniaxial compressive pre-stress of the PZT-BT ceramics are observed at stress levels up to 15 MPa using a uniaxial compressometer. The results clearly show that both the dielectric constant and the dielectric loss tangent of the PZT-BT ceramics increase significantly with increasing applied stress. Larger changes in the dielectric properties with the applied stress are observed in the PZT-rich compositions. The experimental observations have been attributed to the increase of the domain wall motions from the application of the compressive pre-stress. © 2006 Elsevier B.V. All rights reserved.